Conflict Analysis of the Main Characters in Short Stories by Edgar Allan Poe - Maryana Bulu (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2018)
This qualitative research aims to (1) describe the types of conflicts of the main characters in short stories by Edgar Allan Poe, (2) describe the effects of conflicts of the main characters in short stories by Edgar Allan Poe. The researcher used theory by Nurgiyantoro (2002). There are two types of conflicts, internal conflict and external conflict. He divides the external conflict into social conflict and physical conflict. The data source were short stories by Edgar Allan Poe they were: (1) The Tell-Tale Heart (2017), (2) The Black Cat (2017), and (3) The Hop Frog (1849). The data in this study were in the form of main character’s dialogues or utterances, and behavior in the three short stories. Techniques of data analysis done were data reduction, data display, and data conclusion drawing and verification by Miles and Huberman’s theory (1984). The researcher found sixteen data from three short stories by Edgar Allan Poe, there were four data from The Tell-Tale Heart, ten data from The Black Cat, and two data from The Hop Frog, and the details are : Six data of internal conflicts, five data of social conflicts, and five data of physical conflicts. Then, the details of the results on the affects experienced by the main characters are : One datum of positive affect (enjoyment or joy, interest or excitement, and surprise or startle), and fifteen data of negative affect (anger or range, disgust, dissmell, distress or anguish, fear or terror, and shame or humiliation). The researcher expects the next researchers to study concept of conflict analysis or main character in different subjects.